The Influence of Organizational Commitment and Organizational Support on Organizational Citizenship Behavior Mediated by Job Satisfaction - Nur Aisah, Triana; Widhiandono, Hengky; Kharismasyah, Alfato Yusnar; Zamakhsyari, Luthfi (Asian Journal of Management Analytics, 2025)
This study aims to examine the effect of organizational commitment and perceived organizational support on organizational citizenship behavior (OCB), with job satisfaction as a mediating variable. Using a quantitative approach, data were collected through questionnaires from 92 respondents comprising teachers and staff at SMK Muhammadiyah Majenang. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results reveal that both organizational commitment and organizational support significantly influence OCB, both directly and indirectly through job satisfaction. The findings highlight the importance of fostering supportive and value-aligned organizational environments to enhance employees’ discretionary behaviors that contribute to educational effectiveness.